ANALISIS PELAKSANAAN KURIKULUM MERDEKA DI SD NEGERI KEDUNGWARU LOR DEMAK (Adi Widya: Jurnal Pendidikan Dasar, 2023)
The aim of this research is to 1) find out how the independent curriculum is implemented at Kedungwaru Lor Demak State Elementary School; 2) knowing the teacher's understanding of the curriculum structure and independent curriculum learning tools; and 3) knowing the supporting factors and inhibiting factors in implementing the independent curriculum at Kedungwaru Lor Demak State Elementary School. This research uses a qualitative approach with descriptive research type. The subjects of this research are school principals and class I and IV teachers as implementers of the independent curriculum in the 2022/2023 academic year. Data collection techniques were carried out using observation, interviews and documentation. Data analysis techniques are carried out by means of data reduction, data presentation, and data verification. The research results show that 1) In general, the implementation of the independent curriculum at Kedungwaru Lor Demak State Elementary School has been implemented well and is being implemented in stages in grades I and IV in the 2022/2023 academic year; 2) Teachers' understanding of the curriculum structure and independent curriculum learning tools is also quite good, shown by the percentage of achievement for each indicator reaching 83%; 3) Factors inhibiting the implementation of the independent curriculum include difficulties in time management, training regarding the independent curriculum is still limited, and a lack of references, while factors supporting the implementation of the independent curriculum include full support from the school principal, completeness of facilities and infrastructure as well as the enthusiasm of teachers and students in implementing the curriculum independent.